2020
DOI: 10.3390/molecules25051086
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Superoxide Dismutase 1 (Sod1) Linked to Familial Amyotrophic Lateral Sclerosis Can Disrupt High-Affinity Zinc-Binding Promoted by the Copper Chaperone for Sod1 (Ccs)

Abstract: Zinc (II) ions (hereafter simplified as zinc) are important for the structural and functional activity of many proteins. For Cu, Zn superoxide dismutase (Sod1), zinc stabilizes the native structure of each Sod1 monomer, promotes homo-dimerization and plays an important role in activity by “softening” the active site so that copper cycling between Cu(I) and Cu(II) can rapidly occur. Previously, we have reported that binding of Sod1 by its copper chaperone (Ccs) stabilizes a conformation of Sod1 that promotes si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…This mutation was previously found in an fALS patient, but the characterization of its effects has not yet been performed [ 73 ]. The amino-acid substitution P66R occurs at the metal-binding loop of SOD1 [ 74 ], which could hinder binding, preventing CCS action [ 75 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…This mutation was previously found in an fALS patient, but the characterization of its effects has not yet been performed [ 73 ]. The amino-acid substitution P66R occurs at the metal-binding loop of SOD1 [ 74 ], which could hinder binding, preventing CCS action [ 75 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional understanding of Ccs-mediated Sod1 maturation highlights the well-established roles for copper delivery and disulfide bond formation in Sod1 [ 47 ]. We and others have expanded upon this mechanism to include roles for Ccs that include: Sod1 folding, facilitated site-specific zinc acquisition and the formation of a copper drop-off point or “entry-site” upon Sod1 binding [ 41 , 60 , 62 ]. These additional properties separate Ccs from all other known copper chaperones, and thus, Ccs is better characterized as a multifunctional chaperoning molecule with roles in each level of Sod1 maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has also been shown that Ccs binding alone (i.e., without copper delivery) can resolve mis-metalation events where zinc is initially found in the active site. However, some pathogenic Sod1 mutants that cause an inherited form of amyotrophic lateral sclerosis (fALS) seemingly counteract these processes [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…hCCS domain II binds to SOD1 through an ATP-independent mechanism bringing functional hCCS domains I and III into the proximity of nascent SOD1. Full-length and domain II truncated hCCS form heterodimeric complexes with intra-subunit disulphide bond reduced wild-type SOD1 and every ALS mutant directly tested to date [29][30][31][32]. Dissociation constants of 42, 68, 35 and 33 nM have been measured for hCCS binding to metal-free Ala4Val, His80Arg, Gly85Arg and Gly93Ala mutant SOD1, respectively [31].…”
Section: The Copper Chaperone For Sod1mentioning
confidence: 99%
“…Full-length and domain II truncated hCCS form heterodimeric complexes with intra-subunit disulphide bond reduced wild-type SOD1 and every ALS mutant directly tested to date [29][30][31][32]. Dissociation constants of 42, 68, 35 and 33 nM have been measured for hCCS binding to metal-free Ala4Val, His80Arg, Gly85Arg and Gly93Ala mutant SOD1, respectively [31]. Zinc metalated SOD1 forms a heterodimer with hCCS that has higher affinity than the heterodimer formed by metal-free SOD1 [29,32].…”
Section: The Copper Chaperone For Sod1mentioning
confidence: 99%